PERANCANGAN GAME FPP MOUNTAIN CLIMBING LIFE SIMULATION MENGGUNAKAN METODE GDLC - Micheal, Micheal; Simanjuntak, Fredian (Universitas Putera Batam, 2024)
This research aims to design a life simulation game with the theme